Missing in Action: “Framing” Race on Prime-Time Television - Deo, Meera E. (Social justice, 2008)
Part of a special issue on Asian and Pacific Islander populations within the U.S. A study was conducted to analyze the racial ideologies surrounding depictions of Asian and Pacific Islander Americans (APIAs) on prime-time television. Data were obtained through analysis of regular, fictional programming shown on the six broadcast networks. Findings revealed that the presence of APIAs in prime-time network programming was low or nonexistent even when the program's action takes place in areas with significant APIA populations. Findings also revealed that programming with APIA characters tended to reinforce several prevailing stereotypes attached to APIA communities. Findings suggested that prime-time media can and should alter its depictions of such characters to improve representation and alter preconceptions about APIA communities. Findings are discussed in detail.